MISTISISME SEBAGAI JEMBATAN MENUJU KERUKUNAN UMAT BERAGAMA - Wahidi, Ahmad (ULUL ALBAB Jurnal Studi Islam, 2013)
In the history of religion and religious communities has resulted in monumental achievements and noble, which can still be seen today. Any civilization on earth would not be separated from the role of religion and religious people. Meanwhile, today's religious sentiments are often more easily ignited. Many bloody incidents and riots as motivated by understanding and actualization of religion by the religious community. Similarly, many political issues, economy, culture etc. are initially not religious issues suddenly by certain parties associated with religion, so the problem is getting bigger. In such a situation a comprehensive religious view is needed. Formalist-exoteric approach that has dominated the study of religion was not complete even further widened the gap between religious communities because more emphasis on the physical dimensions of these religious symbols. Approaches are possible and must be socialized and adopted is esoteric approach or see substansi of religion, because by looking subsatansi of religion will be able to eliminate the partition of the partition that limits their religious least in terms of his humanity or social relationships between people. One dimension that can be approached is esoteric mysticism, because every religion must have the dimensions of mysticism. And it turns out the substantive similarities of this dimension in any religion.